Relationship Between Energy and Fat Consumption Levels with Metabolic Syndrome Status in Hypertension Patients in Puskesmas Penebel I Tabanan - Ni Putu Diah Arisani; Gusti Ayu Dewi Kusumayanti; Hertog Nursanyoto (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2026)
Metabolic syndrome is a collection of risk factors directly related to non-communicable diseases, the diagnosis refers to the NCEP ATP III criteria, which is characterized by obesity, increased blood sugar, high cholesterol, and high blood pressure. Metabolic syndrome is associated with high energy and fat consumption which can lead to weight gain, insulin resistance, and metabolic disease. The purpose of this study was to determine the relationship between energy and fat consumption levels and metabolic syndrome status in hypertension patients at the Penebel I Health Center. The type of research used was an observational study with a cross-sectional design with the Non Probability Purposive Sampling method. Data were collected using interview and measurement methods. The sample size of the study was 48 people. Based on the results of the study, 27.1% had metabolic syndrome status and 72.9% had no metabolic syndrome status. The results of the Spearman rank test stated that there was a significant relationship between energy consumption levels and metabolic syndrome status with a value (p = 0.016). Then the same test was carried out and obtained results that there was a significant relationship between fat consumption levels and metabolic syndrome status with a value (p = 0.032). The community is expected to reduce fat consumption and routinely check their health at the Health Center.